2008
DOI: 10.1002/ajim.20608
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel surveillance of occupational diseases: A quality improvement project

Abstract: A sentinel surveillance group comprising motivated and guided occupational physicians reported a substantially higher occupational disease incidence and a lower proportion of incorrect notifications than a national registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…So, the extra attention and training for participating OPs contributed to a doubling of the incidence rate for ODs due to NLBP. This raise may be less than expected, since a preceding pilot study showed a sevenfold raise for all ODs in a sentinel group compared with other OPs (Spreeuwers et al., ). However, in this pilot study, participating OPs already had similar numbers of OD notifications in 2 years preceding this study.…”
Section: Discussionmentioning
confidence: 78%
“…So, the extra attention and training for participating OPs contributed to a doubling of the incidence rate for ODs due to NLBP. This raise may be less than expected, since a preceding pilot study showed a sevenfold raise for all ODs in a sentinel group compared with other OPs (Spreeuwers et al., ). However, in this pilot study, participating OPs already had similar numbers of OD notifications in 2 years preceding this study.…”
Section: Discussionmentioning
confidence: 78%
“…It would also be interesting to compare the course of work-related diseases to non-work-related diseases as well as the influence of work-related exposures for the prognosis of diseases. In general, we plea for quality improvement of registries in order to obtain more reliable incidence figures (Spreeuwers et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…The notifications originated from a sentinel surveillance project carried out by the NCvB between 1 October 2003 and 1 July 2005 (Spreeuwers et al 2008). Baseline measurements were made directly after notification and follow-up measurements after 3, 6 and 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Incidence figures for various economic sectors seem to be a promising way to prioritise regulatory and preventive actions. A sentinel surveillance system with a group of motivated OPs was piloted3 and seemed a feasible approach to obtain incidences of ODs in the various economic sectors by assessing both the population of workers and all reported ODs, details of which are lacking in the Dutch National Registry which provides only absolute numbers of cases. Therefore, the main objective of this sentinel surveillance system is to determine the incidence rates of medically reported ODs in The Netherlands in various economic sectors on an annual basis with a sample group of motivated OPs.…”
Section: Introductionmentioning
confidence: 99%